Parent Anxiety Levels In Hospitalization Children In RSUD Majalaya Kab. Bandung - Andria Pragholapati; Della Denita Septiani; Rahmat Sudiyat (UrbanGreen, 2020)
Hospitalization of the child results in anxiety in the parents, this occurs when the child receives nursing procedures, such as blood collection, infusion, injection, and other intensive procedures. The purpose of this study was to identify the level of anxiety in parents with hospitalized children in Majalaya District Hospital. The design of this research is quantitative descriptive. The study population was parents who had children with hospitalization in Majalaya District Hospital, during December totaling 118 people. The research sample of 97 people with a purposive sampling technique. Univariate data analysis method. The results showed that the anxiety level was 58 respondents (59.8%). Parental anxiety in hospitalized children in Majalaya Regional Hospital, in the category that is almost average parents experience moderate anxiety, including experiencing mild and severe anxiety. Patients and parents are expected to request information related to health development from family members who are being treated so as to reduce the anxiety experienced.